Artificial Optimal Fuzzy Control Strategy for Elevator Drive System by Using Permanent Magnet Synchronous Motor - Salam Waley Shneen; Chengxiong Mao (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
There are many power electronic converters and motor drives connected together to form the electrical system of an elevator. In this paper, we have presented a modeling tool that has the advantages of utilizing capabilities of the PMSM software in detailed simulations of converters, motor drives, and electric machines. In addition, equivalent electrical models of Elevator drive system. This paper also gives a brief idea of PMSM validity as an elevator simulation tool. PMSM drive system is described and analyzed due to its importance in many applications especially in elevator applications. applications due to their high efficiency, low inertia and high torque to volume ratio. A closed loop control system with a PI control,Fuzzy, PSO in the speed loop with current controllers .The simulation circuits for PMSM, inverter, speed and current controllers include all realistic components of the drive system. Simulation results for SPWM control schemes associated with current controllers are given for two speeds, one below rated and another above rated speed. in this paper and it has been shown that the model is suitable for transient as well as steady state condition. These results also confirmed that the transient torque and current never exceed the maximum permissible value. DOI: http://dx.doi.org/10.11591/telkomnika.v14i3.7952